Learning in production engineering through games: analysis using ProKnow-c - Nascimento, Lucas Bergami; Oliveira, Kathleen Silvestre de; Servare Junior, Marcos Wagner Jesus; Bragança, Maria Carolina Drago (Brazilian Journal of Production Engineering, 2022)
This study aims to explore the bibliographic portfolio found through the ProKnow-C method, which brings important articles to the topic: A better learning of production engineering at the university through games. The ProKnow-C method refers to a quantitative analysis of published articles carried out through filters such as the reading of pieces and the entirety of the text and the number of citations in Google Scholar, and so on. From this study, 08 articles were identified that are part of the bibliographic portfolio, in which the prominent authors, the means of prominent publications, the material that helped as a basis for the works, in addition to mentioning the contributions of each of them, from learning in higher education to production engineering through games.